Ідентифікація інформативних сигналів у проблемно-орієнтованих розподілених комп'ютерних системах - Кулик, А.Я. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The analysis of efficiency of a filtration informative signals is carried out at their passage by the of communication channel in the problem-oriented allocated computer systems in view of allocation pulse and fluctuation noise.